PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KREATIVITAS DAN HASIL BELAJAR INDUKSI MATEMATIKA - Cahya, R.Aj. Rafika; Sunardi, S; Suharto, S; Susanto, S; Murtikusuma, Randi Pratama (Department of Mathematics Education , University of Jember, 2018)
This research aimed to describe the effect of Problem Based Learning (PBL) on creativity and learning outcomes of mathematical induction. This type of research was quasi-experimental research. This research was conducted on class XI TR and XI AV SMKN 2 Jember. The instruments used were the RPP of the experimental class and the control class, student worksheets, and evaluation of learning outcomes. The data collection methods used in this study was observation and test. To determine the subject of the study, a random technique was used. Based on the result of data analysis, it could be concluded that the students in the experimental class met all indicators well. The students could use several ways to solve the problems. Furthermore, the students were able to find unique ideas to solve the problems. The students expanded, selected, analyzed and evaluated the basic ideas of solving the problems. The students used creative ideas on problem-solving innovations. Keywords: Problem Based Learning, creativity, learning outcomes.